Marcial Suárez’s Testimony about the Third Period of Pontevedra’s Weekly Journal Litoral - Suárez, Mª Luisa (Madrygal. Revista de Estudios Gallegos, 2024)
This article starts by introducing the Galician writer Marcial Suárez (Allariz, 1918 - O Porto do Son, 1996). Thereafter, his own testimony is presented, consisting of two main issues. One of them presents the story of the starting up of the third period of Litoral, the weekly magazine from Pontevedra, led by Domingo Dominguín (1920-1975). A second argument is the description of the last days of the magazine before it was banned by the Francoist regime. This testimony is transcribed from an unpublished manuscript of the author, the last part taking place in Madrid, within the clandestine situation of the Spanish Communist Party. The text that we bring out here is shared as a last discovery in a research on the traces of Litoral, which could be found among the original writings of Marcial Suárez from his personal library.
Keywords: Marcial Suárez; Domingo Dominguín; Galician Weekly Journal; Litoral